Finite element analysis of concrete deep beams with various locations of opening and reinforcement arrangements - Loo, Kian Loon (2017)
Concrete deep beams are very common in structures such as high-rise buildings, foundation and offshore structures. Installation of opening is necessary for accessibility purposes. However, the presence of transverse opening may lead to reduction of beam strength and excessive cracking. In this study, different reinforcement arrangement of concrete deep beams with opening of 100mm diameter at mid-span, shear-span, outside mid-span and shear zone were studied. The software ANSYS 12.0.1 is used to analyses the deep beam models with 0.27 shear-spans to depth ratio to determine the failure loads and crack patterns. Based on the obtained result, the opening located at the shear-span will give the largest effect to the beam strength and crack pattern while the horizontal reinforcement is more effective than vertical reinforcement in the deep beam model with shear-span opening.